Accountability for funds for Nurturing Care: what can we measure?. (12th April 2019) - Arregoces, Leonardo; Hughes, Rob; Milner, Kate M; Ponce Hardy, Victoria; Tann, Cally; Upadhyay, Arjun; Lawn, Joy E
Abstract : Background: Understanding donor, government and out-of-pocket funding for early child development (ECD) is important for tracking progress. We aimed to estimate a baseline for the WHO, UNICEF and World Bank Nurturing Care Framework (NCF) with a special focus on childhood disability. Methods: To estimate development assistance spending, the Organisation for Economic Cooperation and Development's Creditor Reporting System (OECD-CRS) database was searched for 2007–2016, using key words derived from domains of the NCF (good health, nutrition and growth, responsive caregiving, security and safety, and early learning), plus disability. Associated funds were analysed by domain, donor, recipient and region. Trends of ECD/NCF were compared with reproductive, maternal, newborn and child health (RMNCH) disbursements. To assess domestic or out-of-pocket expenditure for ECD, we searched electronic databases of indexed and grey literature. Results: US79.1 billion of development assistance were disbursed, mostly for health and nutrition (US61.9 billion, 78% of total) and least for disability (US0.7 billion, 2% of total). US2.3 per child per year were disbursed for non-health ECD activities. Total development assistance for ECD increased by 121% between 2007 and 2016, an average increase of 8.3% annually. Per child disbursements increased more in Africa and Asia, while minimally in Latin America and the Caribbean and Oceania. We could not find comparable sources for domestic funding and out-of-pocket expenditure. Conclusions: Estimated international donor disbursements for ECD remain small compared with RMNCH. Limitations include inconsistent donor terminology in OECD data. Increased investment will be required in the poorest countries and for childhood disability to ensure that progress is equitable.